STRATEGI PENGEMBANGAN DESA WONOKRITI SEBAGAI DESA WISATA EDELWEIS DI KAWASAN TAMAN NASIONAL BROMO TENGGER SEMERU - Amin Kiswantoro; Dwiyono Rudi Susanto (Journal of Tourism and Economic, 2021)
Edelweis tourism village is one of the tourist villages located in Pasuruan Regency, East Java. This tourist village is still in the Bromo Tengger Semeru National Park area. This tourist village has the main tourism potential, namely the Edelweiss flower or eternal flower. In this research, using descriptive analysis which is qualitative in nature. The data obtained were then analyzed using SWOT analysis. From the results of this study, the development strategy of Wonokriti Village as an Edelweiss tourism village is obtained, including holding activities related to the Edelweiss flower, making this village a center for educational tourism, especially edelweiss flowers, developing tourism supporting infrastructure, holding hospitality training for human resources involved in management. Edelweiss Tourism Village.